(3eSGfjO GHf MLQ GdgjJeis - (3CMeO Hf eMeO Hf Ydj Hf nMnLQ GdngrjnJej GdSYOj GdCfUGQj, TgGH GdOjf TjN GdESdGe, CHh GdYHGS,J (B974 (3g` s
(3ChdgG (B:s
(3hHYO , aEf Gddg JYGdi deG NU MHjHI GdC(B'(3Xe hNdjaJg GdCcHQ GdCYde HLejY OhGFQ GdMGeOjI hGdeMehOjI hEeOGOGJ GdHQjI Hd SGFQ GdNdjbjI HCSQGQg GdYdjI s
(3BNQgG (B:s
(3hef cJH GdSjQ hGdJhGQjN eeG CNPJg Ch LOJg ChQhjJg hGdMeO ddg GdPi gOGfG dgPG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B234 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B152s
Keywords: (3GdJGQjNs